The implementation of Science Technology Society Model to improve students environmental literacy - Supriatna, Encep; Ali, Ismail; Babil, Shahreena; Pratiwi, Intan Dwi (Universitas Negeri Yogyakarta, 2025)
The development of technology is inseparable from the role of humans as creators of culture; technology is a product of creation and human initiative. Technology produced by humans has both positive and negative impacts on humans themselves. The negative effects of this latest technological invention are often used to over-exploit nature and make it easier for humans to meet their daily needs. Awareness of the importance of preserving nature by realizing green behavior or life-friendly behavior towards the environment can be started from the formal education pathway from elementary school to university. To realize awareness about green behavior, knowledge and competence in Environmental literacy are needed. Environmental literacy competence relates to head/mind or aspects of knowledge (learning to know), heart/hand skills (learning to do), and spirit / spiritual (learning to live together). Environmental literacy aims to build a community that agrees on how to understand conceptual ecology in the practice of special education in elementary schools. In addition, it is also an environmental literacy to realize pedagogical processes that are based on local wisdom and directly require the participation of the community in its implementation. The purpose of the research was to improve ecoliteracy in fifth-grade students of Mekarsari State Elementary School, Bogor Regency, West Java. The research used a classroom action research method with 21 fifth-grade students as research subjects. Data collection techniques were carried out by interview, observation, and documentation. The model of interactive qualitative data analysis techniques was conducted to analyze the research. The results of the research showed that the science, technology, and society model could improve the eco-literacy of students of Mekarsari State Elementary School, Pulo Merak, Cilegon from 70 to 76